2003
DOI: 10.1002/cncr.11044
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin prophylaxis in patients with acute leukemia and granulocytopenia in an area with a high prevalence of ciprofloxacin‐resistant Escherichia coli

Abstract: The expression of OL‐protocadherin, a homotypically binding cell adhesion molecule, was mapped in the visual system of the chicken embryo at intermediate to late stages of development (11–19 days of incubation). The expression was compared with that of four classic cadherins, described previously. OL‐protocadherin is expressed by the isthmooptic nucleus, its retinopetal projection, and possibly its retinal target neurons, the amacrine cells. Ganglion cells begin to express OL‐protocadherin at relatively late s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 74 publications
(122 reference statements)
2
31
0
1
Order By: Relevance
“…Currently, no consensus has been made regarding what is considered an appropriate target attainment; ideally, agents and dosages should be chosen that achieve probabilities as close to 100% as possible, without causing untoward toxicity. Increasing MICs and resistance to fluoroquinolones in E. coli and K. pneumoniae have become a greater concern in some parts of the world, including North America, and the lower target attainments found in this analysis reflect changes in MICs often not seen when only percent susceptibility is reported (8,12,28,29). Moreover, because of a higher frequency of A. baumannii and P. aeruginosa isolates for which MICs are elevated, increasing the dose to 400 mg q8h did not significantly improve target attainment, although this dosing regimen was able to maintain target attainments up to AUC/MIC ratios of 250 (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…Currently, no consensus has been made regarding what is considered an appropriate target attainment; ideally, agents and dosages should be chosen that achieve probabilities as close to 100% as possible, without causing untoward toxicity. Increasing MICs and resistance to fluoroquinolones in E. coli and K. pneumoniae have become a greater concern in some parts of the world, including North America, and the lower target attainments found in this analysis reflect changes in MICs often not seen when only percent susceptibility is reported (8,12,28,29). Moreover, because of a higher frequency of A. baumannii and P. aeruginosa isolates for which MICs are elevated, increasing the dose to 400 mg q8h did not significantly improve target attainment, although this dosing regimen was able to maintain target attainments up to AUC/MIC ratios of 250 (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…[3][4][5] Recently, the widespread emergence of FQ-resistant or multidrug-resistant microorganisms in hematologyoncology units has been suggested to compromise the effectiveness of routine antibacterial prophylaxis with FQs in patients undergoing cytotoxic chemotherapy or HCT. [6][7][8][9][10][11][12][13][14] In our center, the isolation rate of FQ-resistant Gramnegative bacilli was high (57.1%) during a period when FQs were routinely administered as antibacterial prophylactic agents; in particular, among isolated Enterobacteriaceae strains, 66.7, 33.3 and 22.2% were resistant to levofloxacin, piperacillin and ceftazidime, respectively. 8 In an attempt to reduce the emergence of antibiotic-resistant microorganisms, we stopped using any antibacterial prophylaxis in both autologous and allogeneic HCT recipients in 2004, 8 and found that this discontinuation of FQ prophylaxis, even in the setting of myeloablative allogeneic HCT did not significantly affect early mortality after transplantation.…”
Section: Introductionmentioning
confidence: 83%
“…Gomez et al reported that the incidence of febrile episodes and bacteremia did not increase when prophylaxis was stopped in another hospital in the same region in Spain. 37 In a third observational study from Spain, there was a tendency for reduced mortality in patients who received levofloxacin compared with patients who received either trimethoprimsulfamethoxazole or no prophylaxis. 38 Long-term surveillance for the development of ciprofloxacin resistance was conducted after a randomized controlled trial of antibiotic prophylaxis in hematologic patients.…”
Section: Local Factors That May Affect Decisions Resistance To Fluoromentioning
confidence: 98%
“…[33][34][35][36][37][38] At a university hospital in Germany 2 attempts to discontinue prophylaxis were stopped because there were more bacteremia and deaths during the periods when prophylaxis was not given. 33,34 Discontinuation of prophylaxis in a Spanish and Swiss hospital 35,36 led to an increase in febrile episodes and bacteremia, but the differences did not reach statistical significance.…”
Section: Local Factors That May Affect Decisions Resistance To Fluoromentioning
confidence: 99%